Downloading plug‐ins for nationalism and cosmopolitanism1. (2nd July 2015) - Tabak, Edin
Abstract A crucial factor in differentiation between existing approaches to nationalism and cosmopolitanism is the positioning of these approaches within a continuum between particularism and universalism, based on their understanding of space and time. However, this also poses a major difficulty in studying practices of nationalism and cosmopolitanism: Reducing these practices to a position within the particularism/universalism continuum establishes different forms of nationalism and cosmopolitanism as 'order of things', through which any practice is projected as an approximation or a distortion of this ideal 'order'. Such a projection tells more about the researchers' own theoretical commitments than the participants' practices. This article utilizes some conceptual tools from Actor‐Network Theory in an effort to establish a sketch for an alternative projection to study practices of nationalism and cosmopolitanism, which will give the participants an opportunity to perform their own time and space, instead of reducing them to placeholders of an already determined position, a priori identified by researchers.